HLA-G in Allergy: Does It Play an Immunoregulatory Role? - Negrini, Simone; Contini, Paola; Murdaca, Giuseppe; Puppo, Francesco (Frontiers in Immunology, 2022)
Allergy is an inflammatory process determined by a cascade of immune events characterized by T-helper 2 lymphocytes polarization leading to interleukin-4 upregulation, IgE secretion, and mast cell and eosinophil activation. HLA-G molecules, both in membrane-bound and in soluble forms, are known to play a key immunoregulatory role and their involvement in allergic diseases is supported by increasing literature data. HLA-G expression and secretion is specifically induced in peripheral blood mononuclear cells of allergic patients after in vitro incubation with the causal allergen. Elevated levels of soluble HLA-G molecules are detected in serum of patients with allergic rhinitis correlating with allergen-specific IgE levels, clinical severity, drug consumption and response to allergen-specific im-munotherapy. HLA-G genetic polymorphisms confer susceptibility to allergic asthma development and high levels of soluble HLA-G molecules are found in plasma and bronchoalveolar lavage fluid of patients with allergic asthma correlating with allergen-specific IgE levels. Interestingly, allergic preg-nant women have lower plasma sHLA-G levels than non-allergic women during the 3rd trimester of pregnancy and at delivery. Finally, in allergic patients with atopic dermatitis HLA-G molecules are expressed by T cells, monocytes-macrophages and Langerhans cells infiltrating the dermis. Although at present is difficult to completely define the role of HLA-G molecules in allergic diseases, it may be suggested that they are specifically expressed and secreted by immune cells during the allergic reaction in an attempt to suppress allergic inflammation.